2021
DOI: 10.1016/j.cgh.2020.11.027
|View full text |Cite
|
Sign up to set email alerts
|

AGA Clinical Practice Update on Palliative Care Management in Cirrhosis: Expert Review

Abstract: BACKGROUND & AIMS:There is debate over whether patients with inflammatory bowel diseases (IBD) treated with biologics that are not tumor necrosis factor antagonists (such as vedolizumab or ustekinumab) should receive concomitant treatment with immunomodulators. We conducted a meta-analysis to compare the efficacy and safety of concomitant immunomodulator therapy vs vedolizumab or ustekinumab monotherapy. METHODS:In a systematic search of publications, through July 31, 2019, we identified 33 studies (6 randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…Given the high prevalence and heavy burden of impaired HRQoL in cirrhosis, attempts have been made to orchestrate treatment algorithm and care trajectory. For instance, the American Gastroenterological Association recently updated their clinical practice on palliative care management in cirrhosis ( 22 ) and recommended a more comprehensive assessment of data around comorbidities, frailty, functional status, and other issues, as the potential for improvement in addition to etiological therapy. This is the case for population‐based prognostic scores such as MELD and Child‐Pugh classification, embracing recognized limitations when applied to individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence and heavy burden of impaired HRQoL in cirrhosis, attempts have been made to orchestrate treatment algorithm and care trajectory. For instance, the American Gastroenterological Association recently updated their clinical practice on palliative care management in cirrhosis ( 22 ) and recommended a more comprehensive assessment of data around comorbidities, frailty, functional status, and other issues, as the potential for improvement in addition to etiological therapy. This is the case for population‐based prognostic scores such as MELD and Child‐Pugh classification, embracing recognized limitations when applied to individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 ) Patients with cirrhosis who develop clinically significant ascites and related complications should be considered for referral for liver transplantation (LT) evaluation and, when appropriate, palliative care. ( 6 )…”
Section: Introductionmentioning
confidence: 99%
“…Numerous tools are available to assess symptoms such as chronic liver disease questionnaire (CLDQ), liver disease quality of life (LDQOL), short form liver disease quality of life (SF-LDQOL), liver disease symptom index (LDSI), liver cirrhosis patient-reported outcome measure (LC-PROM), sickness impact profile (SIP), Edmonton symptom assessment system (ESAS), and patient health questionnaire (PHQ-9). 7 However, there is significant variability in the domains assessed, leading to a lack of standardisation. A meta-analysis by Peng et al 8 showed a significant symptom burden in ESLD with the most frequent symptoms being pain (30-79%), breathlessness (20-88%), erectile dysfunction (53-93%), anxiety (14-45%) and depression (4.5-64%).…”
Section: Symptom Burden In Esldmentioning
confidence: 99%